44.5k views
2 votes
X² + 2x²-3x-6

Get the zeros

User Gibffe
by
5.1k points

2 Answers

6 votes

Answer:

3x^2-3x-6=3(x^2-x-2)=3(x-2)(x+1)

x=2/x=-1

Explanation:

User Tarounen
by
4.6k points
4 votes
Write the polynomial as an equation.
y
=
x
3

2
x
2

3
x
+
6
y
=
x
3
-
2
x
2
-
3
x
+
6
To find the roots of the equation, replace
y
y
with
0
0
and solve.
0
=
x
3

2
x
2

3
x
+
6
0
=
x
3
-
2
x
2
-
3
x
+
6
Replace
y
y
with
0
0
and solve for
x
x
.
Tap for more steps...
x
=
2
,

3
,


3
x
=
2
,
3
,
-
3
The result can be shown in multiple forms.
Exact Form:
x
=
2
,

3
,


3
x
=
2
,
3
,
-
3
Decimal Form:
x
=
2
,
1.73205080

,

1.73205080
X² + 2x²-3x-6 Get the zeros-example-1
User Ismail H
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.